A dopamine-precursor-based nanoprodrug for in-situ drug release and treatment of acute liver failure by inhibiting NLRP3 inflammasome and facilitating liver regeneration. (January 2021) - Zhan, Chenyue; Lin, Guifang; Huang, Yong; Wang, Ziqian; Zeng, Fang; Wu, Shuizhu
Abstract: Acute liver failure (ALF) is a severe liver disease with high mortality rate. Inflammasome is a newly-found and promising target for effective treatment of immunity-associated diseases including liver disease, and dopamine has recently been proved as an inhibitor for NLRP3 inflammasome. This work demonstrates a diselenide-based nanodrug for ALF treatment through inhibiting NLRP3 inflammasome activation and enhancing liver regeneration. A diselenide-containing molecule (DSeSeD) has been synthesized via covalently linking two l -Dopa molecules to a diselenide linker, and the resultant molecules form stable nanoparticles in aqueous media and encapsulate SW033291 (an inhibitor of prostaglandin-degrading enzyme that hampers liver regeneration) to produce the nanodrug (SW@DSeSeD). As a nanoscale prodrug, SW@DSeSeD protects its payloads from decomposition in bloodstream upon administration, accumulates in liver of ALF mice, then responds to the overexpressed ROS and thereby releases SW033291 as well as a stable dopamine precursor that can transform into dopamine in hepatic cells, thus achieving significant therapeutic efficacy against ALF through inhibiting NLRP3 inflammasome activation and enhancing hepatic regeneration. Moreover, multiple contrast agents have been loaded onto the nanodrug to achieve fluorescence, optoacoustic and magnetic resonance imaging for nanodrug location and disease evaluation. Graphical abstract: Image 1 Highlights: An inflammation-responsive nanoprodrug has been developed for ALF treatment. The nanodrug releases dopamine precursor and SW033921 for NLRP3 inflammasome inhibition and for liver regeneration. Multiple contrast agents loaded onto the nanodrug can track its biodistribution and monitor liver function evolution.